Correlation of nerve conduction study parameters with thyroid hormone in newly diagnosed hypothyroid patients - Gupta, Shital; Khadka, Rita; Thakur, Dilip; B. H. Paudel; Maskey, Robin; K. D. Mehta (Asian Journal of Medical Sciences, 2021)
Background: Thyroid hormones act on many organs including central and peripheral nervous system for maintaining metabolic homeostasis. Entrapment neuropathies are most common in hypothyroidism. Nerve conduction parameters are impaired even in newly diagnosed cases of hypothyroid. Aims and Objectives: This study aims to study the correlation between thyroid hormone and nerve conduction study (NCS) parameters in newly diagnosed hypothyroid patients. Materials and Methods: This cross-sectional, descriptive study included newly diagnosed hypothyroid patients (n=30; age: 31.96±9.12). In all subjects, NCS was performed in median, ulnar, tibial motor nerve and median, ulnar, sural sensory nerve using Nihon Kohden machine in Neurophysiology lab 2, B. P. Koirala Institute of Health Science. Thyroid function test (TFT) was analyzed by ELISA. The association between thyroid hormone and NCS parameters was done using Pearson’s correlation. Results: In NCS sensory parameters; SNAP amplitude of the left sural nerve showed significant positive correlation with t3 (lt; r=0.451, P=0.012). Among motor parameters, distal latency of left median nerve showed significant negative correlation with t3 whereas nerve conduction velocity of the left median nerve showed positive correlation with t3. In rest of the nerve, the association between NCS parameters and TFT (t3, t4, and TSH) parameters did not show any significant changes. Conclusion: Our study reveals that in newly diagnosed cases of hypothyroidism, nerve impairment occurs in which the left side is affected much earlier than right side and further its severity can be correlated with level of T3 rather than TSH.